Acceptance and Commitment Therapy (ACT) as a Counselling Strategy for Reducing Post-Traumatic Stress Disorder Associated with Rape (Journal of Guidance and Counselling Studies, 2025)
Rape is an unlawful sexual intercourse between a man and a woman, and the act is becoming very rampant in Nigeria. Most of the time, perpetrators go unpunished, while most rape survivors develop Post-Traumatic Stress Disorder (PTSD), leading to social, psychological, and emotional pains. Rape victims thus require therapeutic intervention to adjust to this situation. This paper therefore highlights the usefulness of Acceptance and Commitment Therapy (ACT) as a counselling strategy for mitigating PTSD among victims of rape. ACT is designed to defuse emotional rigidity and emphasises engaging clients in value-based positive behaviours while experiencing difficult thoughts, emotions, or sensations. It is a therapeutic approach used in helping rape victims overcome emotional and psychological trauma, such as hopelessness, low self-esteem, suicidal ideation, self-blame, and flashbacks. The paper also covers a review of relevant literature on the concepts of rape, theories of rape, rape trauma syndromes, as well as the application of ACT in reducing PTSD among rape victims in Nigeria. Based on the review, it was suggested that counsellors in Nigeria should adopt ACT in assisting rape victims to cope with the challenges associated with PTSD.
Keywords: Acceptance and Commitment Therapy; Post-Traumatic Stress Disorder; Rape; Counselling strategy